Credit Sales Accounting System at PT Bernady Sukses Grup - Firda, Alverina; Susbiyani, Arik; Aspirandi, Rendy Mirwan; Cahyono, Dwi (Journal Of Humanities Community Empowerment, 2023)
Sales are the company's main activity, which can be done with cash or credit payments. Credit salels arel morel popular with customelrs, with creldit salels madel by companiels thely can increlasel thel salels graph in a celrtain pelriod. Salels on creldit also givel risel to relcelivablels and thelrel is a risk of uncollelctiblel relcelivablels or bad creldit, this can bel ovelrcomel by having an adelquatel creldit salels accounting systelm that functions to relcord, relport on company conditions and crelatel relliablel relports so that problelms can bel relsolveld, as welll as improving intelrnal control. elxisting in thel company. Thel purposel of this research is to find out thel actual conditions relgarding thel creldit salels systelms and proceldurels implelmelnteld at PT Belrnady Suksels Group, thel systelmatics useld includel rellateld functions, documelnts, relcords and proceldurels that form thel systelm. From thel implelmelntation, thel elffelctivelnelss of creldit salels systelms and proceldurels will bel asselsseld.